2020
DOI: 10.1515/cclm-2020-1178
|View full text |Cite
|
Sign up to set email alerts
|

Harmonization of antineutrophil cytoplasmic antibodies (ANCA) testing by reporting test result-specific likelihood ratios: position paper

Abstract: To the Editor, Antineutrophil cytoplasmic antibodies (ANCA) are valuable laboratory markers to support the diagnosis of ANCAassociated vasculitis (AAV). High-quality immunoassays for proteinase-3 (PR3)-ANCA and myeloperoxidase (MPO)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…With respect to harmonization, the multicenter study that was the basis of the revised consensus, interestingly, revealed that if results were reported in terms of likelihood ratios for test result intervals that were defined by pre-set levels of specificity, the likelihood ratios were very similar for the different assays included in the study (18). The level of harmonization that can be achieved by this approach is very promising and even resulted in a position paper, signed by relevant stakeholders in ANCA testing, that proposes to employ test result-specific likelihood ratios to align test result interpretation across assays and manufacturers and to convey clinical information intrinsic to the antibody level (19). Reporting test results as likelihood ratio will greatly facilitate interpretation of the results in the context of the clinical presentations of the patients, since there is a clear relationship, as defined by the Bayes theorem, between pre-test probability, likelihood ratio and post-test probability (47).…”
Section: Standardization Vs Harmonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to harmonization, the multicenter study that was the basis of the revised consensus, interestingly, revealed that if results were reported in terms of likelihood ratios for test result intervals that were defined by pre-set levels of specificity, the likelihood ratios were very similar for the different assays included in the study (18). The level of harmonization that can be achieved by this approach is very promising and even resulted in a position paper, signed by relevant stakeholders in ANCA testing, that proposes to employ test result-specific likelihood ratios to align test result interpretation across assays and manufacturers and to convey clinical information intrinsic to the antibody level (19). Reporting test results as likelihood ratio will greatly facilitate interpretation of the results in the context of the clinical presentations of the patients, since there is a clear relationship, as defined by the Bayes theorem, between pre-test probability, likelihood ratio and post-test probability (47).…”
Section: Standardization Vs Harmonizationmentioning
confidence: 99%
“…As such, it is most appropriate to use quantitative assays, while keeping in mind that the assays are primarily designed for diagnostic purposes. For diagnosis quantitative ANCA results are important because higher ANCA levels are associated with higher likelihood ratios and, therefore, with increased certainty of the right diagnosis (18,19). For follow-up it is important to monitor possible decreases in ANCA levels upon therapy, but also to monitor possible increases as potential predictor for an upcoming relapse (10,11).…”
Section: Implementation Of Anca Assays In Clinical Practicementioning
confidence: 99%
“…Another advantage of using LRs is the harmonization of different techniques, scales, units etc. (24). It certainly would make it easier for the clinician to interpret one single scale, namely LR, than having to get acquainted with different titers, units/ml, ug/ml, mmol/l etc.…”
Section: What Needs To Be Done?mentioning
confidence: 99%
“…But often, especially in non-harmonized test systems and when the result is at a level near the cut-off point between positivity and negativity, the information content of the result will be overestimated and therefore misleading. As an example, we recently defined for 8 different ANCA test systems assayspecific test results that corresponded to a LR of 0.1, 1, 10 and 30 (24). For the different assays, the test result that corresponded to a LR of 10 was 35 Units, 48.5 CU, 8.6 IU/mL, 2.8 AI, 10 IU/mL, 13.8 U/mL, 48 U/mL and 10.7 IU/mL (24).…”
Section: What Needs To Be Done?mentioning
confidence: 99%
See 1 more Smart Citation